Non-sterile fermentation of food waste using thermophilic and alkaliphilic Bacillus licheniformis YNP5-TSU for 2, 3-butanediol production. (1st February 2021) - OHair, Joshua; Jin, Qing; Yu, Dajun; Wu, Jian; Wang, Hengjian; Zhou, Suping; Huang, Haibo
Highlights: Nonsterile food waste was fermentated to produce 2, 3-butanediol (2, 3-BDO). Fermentation was conducted under alkaline and thermophilic condition. Novel Bacillus licheniformis YNP5-TSU from Yellowstone National Park was used. YNP5-TSU produced high yields of 2, 3-BDO (0.38–0.41 g/g) from food waste sugars. YNP5-TSU could ferment food waste without addition of external nutrients. Abstract: Conversion of food waste into 2, 3-butanediol (2, 3-BDO) via microbial fermentation provides a promising way to reduce waste disposal to landfills and produce sustainable chemicals. However, sterilization of food waste, an energy- and capital-costly process, is generally required before fermentation to avoid any contamination, which reduces the energy net output and economic feasibility of food waste fermentation. In this study, we investigated the non-sterile fermentation of food waste to produce 2, 3-BDO using a newly isolated thermophilic and alkaliphilic B. licheniformis YNP5-TSU. Three unitary food waste samples (i.e., pepper, pineapple, cabbage wastes) and one miscellaneous food waste mixture were respectively inoculated with B. licheniformis YNP5-TSU under non-sterile conditions. At 50 °C and an initial pH of 9.0, B. licheniformis YNP5-TSU was able to consume all sugars in food waste and produce 5.2, 5.9, 5.9 and 4.3 g/L of 2, 3-BDO within 24 h from pepper, pineapple, cabbage and miscellaneous wastes, respectively, corresponding to a yield of 0.40, 0.38, 0.41 and 0.41 g 2, 3-BDO/g sugar. These 2, 3-BDO concentrations and yields from the non-sterile fermentations were comparable to those from the traditional sterile fermentations, which produced 4.0–6.8 g/L of 2, 3-BDO with yields of 0.31–0.48 g 2, 3-BDO/g sugar. Moreover, B. licheniformis was able to ferment various food wastes (pepper, pineapple and miscellaneous wastes) without any external nutrient addition and produce similar 2, 3-BDO quantities. The non-sterile fermentation of food waste using novel thermophilic and alkaliphilic B. licheniformis YNP5-TSU provides a robust and energy-efficient approach to convert food waste to high-value chemicals.